Determinants of Carbon Emission Disclosure in State-Owned and Private Enterprises - Riyono, Kenley Maccauley; Stanley, Nicklaus; Widianingsih, Luky Patricia (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2026)
This study aims to provide empirical evidence on the determinants of CED, with total carbon emissions as a moderating variable in state-owned and private enterprises. The method used is moderate regression analysis. The results of this study indicate that there is no single determinant that has a significant effect on CED in state-owned enterprises. However, total carbon emissions interact with board size in relation to CED. In private enterprises, CEO narcissism, capital expenditure, and media exposure has a significantly positive effect on CED, with total carbon emissions interacting only with capital expenditure. Foreign CEOs have a significant negative effect on CED, interacting with total carbon emissions. Board size, female CEO presence, and productivity do not have a significant impact on CED. The findings provide guidance for management on factors to enhance CED while supporting greater transparency and accountability in enterprises. This helps address carbon emissions in Indonesia to support a green and blue economy.